Medicaid managed care enrollment report : summary statistics as of June 30 ... - United States. Health Care Financing Administration; Centers for Medicare & Medicaid Services (U.S.) (Baltimore, Md. : Health Care Financing Administration)
Provides data on each plan that provides managed care services to Medicaid recipients. For each plan, information on whether the plan is statewide, the plan's program type, payment arrangement, waiver type (if applicable), population covered, and the number of enrollees is provided.
Description based on: 1995; title from "Medicaid Managed Care" home page (viewed July 2, 2001).
Latest issue consulted: 2003.
PDF, HTML and Excel formats.
Also issued in print.
System requirements: Adobe Acrobat software which is available for download and optional Excel software (for some earlier issues).
Mode of access: Internet at the Centers for Medicare & Medicaid Services web site (contents in PDF and HTML versions, and some earlier issues have files in self-extracting zip format). Address as of Dec. 1, 2004: http://www.cms.hhs.gov/medicaid/mcaidsad.asp; current access is available via PURL.
Keywords: Managed care plans (Medical care) -- United States -- Statistics -- Periodicals; Medicaid -- Statistics -- Periodicals; Medicaid -- statistics & numerical data; United States; Managed Care Programs -- statistics & numerical data; Statistics